The US-China Trade War and the Relocation of Global Value Chains to Mexico - Utar, Hâle; Zurita, Alfonso Cebreros; Torres, Luis (The Review of Economics and Statistics, 2025)
Abstract We examine how the 2018–19 US–China trade war affected Mexican firms' trade and find that US tariff hikes on China increased exports to the US, imports from the US and Asia, and net exports overall. Distinguishing firms by global value chain (GVC) participation and parent country, we show that foreign multinationals in technology-intensive industries drove much of the adjustment. Heterogeneous responses between US and non-US MNEs highlight nearshoring dynamics and GVC reorganization toward Mexico. The results provide firm-level evidence of trade policy's transformative effects on GVCs and the role of MNEs in transmitting policy spillovers to third countries.